2011
DOI: 10.1523/jneurosci.6156-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Basis for Diminished Functional Recovery after Delayed Peripheral Nerve Repair

Abstract: The postsurgical period during which neurons remain without target connections (chronic axotomy) and distal nerve stumps and target muscles are denervated (chronic denervation) deleteriously affects functional recovery. An autologous nerve graft and cross-suture paradigm in Sprague Dawley rats was used to systematically and independently control time of motoneuron axotomy, denervation of distal nerve sheaths, and muscle denervation to determine relative contributions of each factor to recovery failure. Tibial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
252
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(271 citation statements)
references
References 62 publications
4
252
0
4
Order By: Relevance
“…Motor neurons in the spinal cord survive peripheral transection [10] due to tropic support from Schwann cells in the proximal nerve and from re-innervated muscle after chronic injury [4]. We did not observe motor deficits after delivery of a Wnt pathway inhibitor, demonstrating that loss of MN in our model was wortmannin specific and likely represents suicide transport.…”
Section: Spine Research Issn 2471-8173mentioning
confidence: 73%
See 1 more Smart Citation
“…Motor neurons in the spinal cord survive peripheral transection [10] due to tropic support from Schwann cells in the proximal nerve and from re-innervated muscle after chronic injury [4]. We did not observe motor deficits after delivery of a Wnt pathway inhibitor, demonstrating that loss of MN in our model was wortmannin specific and likely represents suicide transport.…”
Section: Spine Research Issn 2471-8173mentioning
confidence: 73%
“…Current therapies are inadequate in current animal models of spinal cord injury (SCI) [1][2][3][4][5][6][7]. A common objective is to mimic clinical SCI by generating a chaotic wound through cord laminectomy followed by controlled impact [2].…”
mentioning
confidence: 99%
“…In fact, since prevention of muscle atrophy and degeneration is a key issue for successful func-tional recovery after nerve injury [44], it is very important that the regenerated axons reach their target as much rapidly as possible. In this view, the effects, both direct or glial cell-mediated, on neurite elongation exerted by NRG1 could represent a very positive tool on axonal regeneration after nerve injury in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…During these studies it was observed that the administration of FK506, at concentrations far below that required for its immunosuppressant function (5 mg/kg/day down to 0.05 mg/kg/day for 4 weeks), influenced axon regeneration. FK506 (1) induces a 2-fold increase in the number of axons that regenerate, (2) increases the speed of axon regeneration across 4 cm gaps, (3) increases the number of myelinated axons by 40% , (4) significantly increases myelin thickness, (5) increases the specificity of sensory and motor target reinnervation, and (6) increases the extent of neurological recovery [346][347][348][349][350][351][352][353][354][355][356].…”
Section: Immunosuppressantsmentioning
confidence: 99%